Niveles de incremento y rendimiento maderable de poblaciones naturales de Pinus arizonica Engl., de El Poleo, Chihuahua - Zepeda Bautista, E. Marcelo; Domínguez Pereda, Alfonso (Instituto de Ecología, A.C., 2016)
A first dasometric analysis using data from permanent plots was made around the early 70's at El Poleo, in Chihuahua State. The results consist of a set of dasometric equations allowing the estimation of the average behavior along time, of growth, yield and possible survival of the stands represented in the sample. Such equations initially allow us to know the net growth and yield wood of those stands, with the obvious advantage for operative silvicultural management of stands from El Poleo, Madera, Chihuahua.